Cannabis Contaminants Limit Pharmacological Use of Cannabidiol - Montoya, Zackary; Conroy, Matthieu; Vanden Heuvel, Brian D.; Pauli, Christopher S.; Park, Sang-Hyuck (Frontiers in Pharmacology, 2020)
For nearly a century, Cannabis has been stigmatized and criminalized across the globe, but in recent years, there has been a growing interest in Cannabis due to the therapeutic potential of phytocannabinoids. With this emerging interest in Cannabis, concerns have arisen about the possible contaminations of hemp with pesticides, heavy metals, microbial pathogens, and carcinogenic compounds during the cultivation, manufacturing, and packaging processes. This is of particular concern for those turning to Cannabis for medicinal purposes, especially those with compromised immune systems. This review aims to provide types of contaminants and examples of Cannabis contamination using case studies that elucidate the medical consequences consumers risk when using adulterated Cannabis products. Thus, it is imperative to develop universal standards for cultivation and testing of products to protect those who consume Cannabis.